2020
DOI: 10.3892/br.2020.1303
|View full text |Cite
|
Sign up to set email alerts
|

Tissue gene mutation profiles in patients with colorectal cancer and their clinical implications

Abstract: Colorectal cancer (CRC) is one of the most common types of cancer in the world, and targeted therapy is frequently used in the clinical management of the disease. A complete and accurate picture of tissue gene mutations is therefore critical. Tissue specimens from 117 patients with CRC were used for high throughput DNA next-generation sequencing (NGS) analysis. Hotspots from 50 genes frequently associated with the development and progression of solid tumors were targeted for sequencing. Characterization of tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…KRAS amplification in CRC is a rare event, with an overall prevalence of 0.67–2% ( 11 , 12 ). Previous studies have identified somatic mutations in KRAS as biomarkers for inherent resistance to EGFR-targeted drugs in patients with CRC ( 13 ), with a positive tissue mutation rate of 32–52.1% ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…KRAS amplification in CRC is a rare event, with an overall prevalence of 0.67–2% ( 11 , 12 ). Previous studies have identified somatic mutations in KRAS as biomarkers for inherent resistance to EGFR-targeted drugs in patients with CRC ( 13 ), with a positive tissue mutation rate of 32–52.1% ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In one of our cases, there was a mutation in the tumour suppressor gene RB1, which are present in 5.8% of all colorectal cancers (14,15). To date, no statistically significant impact of RB1 gene mutations on patient prognosis in colorectal cancer has been shown [31]. In addition to CTNNB1 and RB1, a PIK3CA mutation was found in one of the two neoplasms.…”
Section: Woischke Et Almentioning
confidence: 54%
“…However, a few studies have revealed that the APC gene may have a different performance, with a few detected SNPs in exon 15 of this tumor suppressor gene as a germline mutation 19,[29][30][31][32] . A most recent study on common gene mutation profile in CRCs showed point mutations in exon 16 of APC gene with a 19.7% prevalence 29,[33][34][35] . Although APC has been well-recognized as an initiator gene in colorectal cancer carcinogenesis, its prognostic role has not been well-established.…”
Section: Discussionmentioning
confidence: 99%